Derivational Affixes and Their Functions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Derivational affixes are linguistic elements that attach to a base or root word to create new words, often with a shift in meaning or grammatical category. These affixes play a crucial role in the morphological structure of language, enabling speakers to expand their vocabulary and convey nuanced meanings. They can be classified into prefixes, suffixes, infixes, and circumfixes, each serving specific functions within word formation. The function of derivational affixes includes altering the syntactic category of the base word (e.g., turning a verb into a noun or an adjective into an adverb) and changing the meaning of the root word (e.g., denoting negation, intensification, or causation). In this paper, we explore the different types of derivational affixes, their syntactic and semantic roles, and their impact on the morphological structure of languages. Through this examination, we highlight the importance of derivational affixes in language evolution, word creation, and communication efficiency.